Recent advances in mammalian protein production. Issue 2 (6th December 2013) - Bandaranayake, Ashok D.; Almo, Steven C.
Abstract : Mammalian protein production platforms have had a profound impact in many areas of basic and applied research, and an increasing number of blockbuster drugs are recombinant mammalian proteins. With global sales of these drugs exceeding US$120 billion per year, both industry and academic research groups continue to develop cost effective methods for producing mammalian proteins to support pre‐clinical and clinical evaluations of potential therapeutics. While a wide range of platforms have been successfully exploited for laboratory use, the bulk of recent biologics have been produced in mammalian cell lines due to the requirement for post translational modification and the biosynthetic complexity of the target proteins. In this review we highlight the range of mammalian expression platforms available for recombinant protein production, as well as advances in technologies for the rapid and efficient selection of highly productive clones.